When masses meet markets: credentialism and commodification in twenty-first century Higher Education. Issue 2 (4th March 2022) - Tomlinson, Michael; Watermeyer, Richard
ABSTRACT: The institutional form and conception of Higher Education have changed through the growth of mass higher education, which in many national systems now operates on market logics. Drawing on theories of credentialism, this article provides a critical analysis of the inter-relationship between massification and marketization and examines a range of consequences this has for institutional relations and dynamics. A central feature of credential inflation in mass systems has been the growing competition for scarce status goods and the reproduction of structural inequalities in accessing sought-after occupational outcomes. The policy context of marketization has concurrently reinforced the pressures on institutions to fulfil the promise held by governments, employers and graduates of enhancing human capital and Higher Education institutions' economic value. Accompanying New Public Management policy levers have further established institutional conditions based on competitive accountability and performative evaluation. We show how these pressures are manifested in new forms of instrumental rationality that valorize the commodification of academic credentials, and relatedly, studentship and academic scholarship. We finally consider the possible ways forward in appraising the goals of HE beyond credential inflation.